Rancang Bangun Mesin Pengupas Kulit Buah Nanas Menggunakan Penggerak Motor Listrik - Habibur Rahman (INOVTEK - SERI MESIN, 2022)
In general, the process of peeling pineapple skin in the community still uses traditional methods, where the traditional method has several drawbacks, namely a small work capacity where to peel one pineapple takes ± 1-2 minutes. Stripping in this traditional way still has many shortcomings and weaknesses, including requiring a large amount of energy, requiring people who have special skills, risk of being hit by a knife, taking a long time, and the stripping position is not ideal. Design and manufacture a pineapple peeling machine with variations for peeling pineapples of various sizes. To find out how efficient the pineapple peeling machine is. This research was carried out based on four stages, the first was field observation, the second was design and design, the third was machine assembly, and the last was testing. This pineapple peeling machine is driven by a 0.5 hp electric motor with 1380 rpm and with a fruit chuck and stainless steel blade so that the material does not rust. This machine is designed to simplify and speed up the pineapple peeling process with a capacity of 96 pieces/hour . The stripping shaft rotation is 138 rpm and the engine speed is 1380. The efficiency of the pineapple peeling machine with a hollow galvanized iron frame material measuring 3 x 3 cm is able to support the machine and components of the pineapple peeling machine so as not to affect the results of the pineapple peeling.